2015
DOI: 10.22319/rmcp.v6i3.4090
|View full text |Cite
|
Sign up to set email alerts
|

Use of bee pollen in broiler diet

Abstract: El polen de abeja (PA) puede ser un complemento nutricional para los animales, ya que mejora la eficiencia del uso de nutrientes, lo que aumenta su absorción, acelera el crecimiento de los animales y mejora su rendimiento productivo. El efecto del PA en la dieta de pollos de engorda se evaluó sobre la digestibilidad, rendimiento, mucosa intestinal y calidad de la cama. Para evaluar la digestibilidad, se utilizaron 200 aves en un diseño de bloques al azar con cuatro tratamientos (0, 0.5, 1.0 y 1.5 % de inclusió… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
1
1
0
5
Order By: Relevance
“…Moreover, the duration of the experiments and the different formulations among the feeds may also have contributed to such differences. Our findings corroborate with diverse studies carried out with other animal categories such as quails (Faria et al, ), poultry (Oliveira et al, ) and country chickens (Araújo et al, ) which showed no improvement on animal performance neither negative effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the duration of the experiments and the different formulations among the feeds may also have contributed to such differences. Our findings corroborate with diverse studies carried out with other animal categories such as quails (Faria et al, ), poultry (Oliveira et al, ) and country chickens (Araújo et al, ) which showed no improvement on animal performance neither negative effects.…”
Section: Discussionsupporting
confidence: 93%
“…There are relevant studies reporting the use of this additive in several animal categories, including Japanese quails (Faria et al, 2008), rabbits Attia, Al-Hanoun, El-Din, Bovera, & Shewika, 2011;Zeedan, Battaa, Abuoghaba, & El-Kholy, 2017), rats (Hajková et al, 2013;Selmanoğlu, Hayretdağ, Kolankaya, Tuylu, & Sorkun, 2009), commercial chickens (Henriques et al, 2014;Nascimento et al, 2015;Oliveira et al, 2015;Rodrigues et al, 2018) and country chickens (Araújo et al, 2017). The bee pollen has already been tested on fish in traditional open systems (usually with low stocking densities) with satisfactory performance results (Abbass, El-Asely, & Kandiel, 2012; El-Asely, Abbass, & Austin, 2014).…”
mentioning
confidence: 99%
“…O pólen apícola apresenta diversas propriedades nutricionais e medicinais como uma substância antienvelhecimento e antioxidante para melhorar as funções PUBVET v.13, n.12, a471, p.1-10, Dez., 2019 imunológicas e o crescimento do animal, além de melhora a produção de leite e a taxa de sobrevivência da prole (Dias et al, 2013;Tu et al, 2015). Fazayeli-Rad et al (2015) e Oliveira et al (2015) concluíram que o pólen pode ser um complemento nutricional para os animais, pois melhora a eficiência do uso de nutrientes, aumentando sua absorção e acelerando o crescimento dos animais, melhorando seu desempenho produtivo capaz de melhorar o status imunológico do animal, sem aumentar o custo final da dieta. Attia et al (2011a) concluíram que a melhor concentração de pólen em dietas de coelho e de 200 mg/kg de peso corporal.…”
Section: Pólen Apícolaunclassified
“…Diversos estudos foram realizados com esse aditivo funcional em outras categorias animais, principalmente aves (Faria et al, 2008;Rodrigues et al, 2018;Henriques et al, 2014;Nascimento et al, 2015;Oliveira et al, 2015;Araújo et al, 2017). No entanto, poucos estudos foram realizados quanto ao seu uso em dietas aquícolas.…”
Section: Amostra Um (%) MM (%) Lpd (%) Ptn (%) Frut (%) Glc (%)unclassified
“…Existem relevantes estudos com o uso deste aditivo para diversas categorias animais (Wang et al, 2007;Faria et al, 2008;Selmanoglu et al, 2009;Attia et al, 2011a;Attia et al, 2011b;Hajková et al, 2013;Henriques et al, 2014;Nascimento et al, 2015;Oliveira et al, 2015;Araújo et al, 2017;Zeedan et al, 2017;Rodrigues et al, 2018), no entanto, são escassos os estudos com a utilização do pólen para peixes.…”
Section: Introductionunclassified